Changes of fungal diversity in fine coal gasification slag amendment pig manure composting. (April 2021) - Liu, Tao; Kumar Awasthi, Mukesh; Jiao, Minna; Kumar Awasthi, Sanjeev; Qin, Shiyi; Zhou, Yuwen; Liu, Huimin; Li, Ji; Zhang, Zengqiang
Graphical abstract: Highlights: Effect of fine coal gasification slag (FCGS) on fungal community was studied. 4% FCGS was the smallest operational taxonomic unit among all treatments. Ascomycota (91.73%) and Basidiomycota (7.75%) were the main fungal phyla. 10% FCGS was a potential concentration to enhance fungal diversity. Abstract: The purpose of this study was to investigate fungal diversity and relative abundance (RA) during pig manure composting via high-throughput sequencing approach. Fine coal gasification slag (FCGS) (0%, 2%, 4%, 6%, 8% and 10%) were added into composting raw materials as additive and performed 42 days. Adjust C/N and moisture to 30 and 65%. Results showed that dominant phyla were Ascomycota (99.62%) and Basidiomycota (0.38%). The main genera were Epicoccum (1.26%), Alternaria (83.35%), Aspergillus (12.08%) and Gibberella (1.69%). 10% treatment got the higher abundance and operational taxonomic units number from rank abundance curve and petals diagram. Compared with control, FCGS amendment composting could increase the sanitary time (3–7 d) and total nitrogen (0.05–12.03%). The principal component analysis was considered that FCGS treatments and control had significantly difference. The RA of fungi varied among all treatments. Therefore, 10% treatment was a potential candidate to enhance fungal diversity and composting quality.